Prostatic hyperplasia and congenital bladder diverticulum. A case report - Ciro Esteban Delgado Cantero; María Raquel Abreu Santana (Medisur)
Congenital diverticula in adults are typically associated with bladder outlet obstruction and their manifestation is most commonly by urinary sepsis. The case of a 69 years old male patient who attended consultation because of nocturia, thin urine stream, pushing, urgent urination and sense of incomplete emptying is presented. Through rectal examination grade I prostate with discrete grade I asymmetry consistent with right nodular lobe that did not rise to the surface was detected. During the physical examination tumor mass was palpated in the lower abdomen region. It was painless. Ultrasound and cystography showed giant bladder diverticulum with a narrow neck into the right lateral wall of the bladder. Cystoscopy confirmed the diagnosis and the patient was treated trough surgery. Histology revealed mucosal layers and muscle and adventitia in the wall, thus confirming congenital origin. Recovering after surgery was satisfactor.